2018
DOI: 10.1242/jeb.176909
|View full text |Cite
|
Sign up to set email alerts
|

The essential oil of Lippia alba and its components affect Drosophila behavior and synaptic physiology

Abstract: is a flowering shrub in the verbena family and its essential oil (EO) is known for its sedative, antidepressant and analgesic properties. In the Amazon region of Brazil, it is used in aquaculture to anesthetize fish during transport. Many of the specialized metabolites found in EOs presumably evolved to protect plants from herbivores, especially insects. We used to test the behavioral and physiological actions of this EO and its components. We found that a 150 min exposure to the EO vapors resulted in immobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
(73 reference statements)
1
7
0
Order By: Relevance
“…The result of GC-MS analysis revealed the presence of 2, 7 octadione-1butoxy, 2-isopropenyl-5-methyl hex-4-enol, aromadendrene oxide and caryophyllene oxide as major compounds (Table 5). But the previous reports of GC-MS analysis had implied the presence of citral, carvone, limonene as the major compounds in the essential oil of L. alba (da Silva et al 2018). This variation in the composition might be depended on topographical as well as climatic condition Ngassapa et al (2003) of the place where the plant grows.…”
Section: Discussionmentioning
confidence: 97%
“…The result of GC-MS analysis revealed the presence of 2, 7 octadione-1butoxy, 2-isopropenyl-5-methyl hex-4-enol, aromadendrene oxide and caryophyllene oxide as major compounds (Table 5). But the previous reports of GC-MS analysis had implied the presence of citral, carvone, limonene as the major compounds in the essential oil of L. alba (da Silva et al 2018). This variation in the composition might be depended on topographical as well as climatic condition Ngassapa et al (2003) of the place where the plant grows.…”
Section: Discussionmentioning
confidence: 97%
“…The GC/MS analysis of all essential oils resulted in the detection of 57 constituents. Thirty‐one of these compounds were found in the essential oil of L. alba , the main constituents being α‐citral (32.32 %) and β‐citral (23.19 %), being the same compounds reported as majorities in another study involving L. alba [14] . In L. thymoides essential oil 31 compounds were detected mainly composed by eucalyptol (14.41 %) and borneol (11.63 %).…”
Section: Resultsmentioning
confidence: 62%
“…Increased intracellular Ca 2+ level stimulates the actuation of inflammatory pathways and cell death, particularly over mitochondria insufficiency (Ganjiani et al, 2021). At this point, da Silva et al (2018) reported that citral has a preventative effect on the influx Ca 2+ release in cells by blocking the voltage‐gated Ca 2+ channels (da Silva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%